Lair of the Wolven : Forever - Book 2 - Ward, J. R., 1969- (New York : Pocket Books, 2023)
For Lydia Susi, there is no sweet sorrow in saying goodbye to the man she loves...As an operative for a clandestine arm of the United States government, Daniel Joseph always expected to die an early death. He just assumed it would be out in the field--not in a laboratory hospital bed. With his time running out, he refuses a potentially lifesaving treatment to focus on making sure that Lydia finds her wolven clan...Marshaling his strength, he must call on all of his training to protect his love...even if it means her moving on without him"--
Keywords: Wolves -- Fiction; Man-woman relationships -- Fiction; Fantasy fiction; Romance fiction; Novels